1995
DOI: 10.1128/mcb.15.10.5607
|View full text |Cite
|
Sign up to set email alerts
|

Replication Slippage between Distant Short Repeats in Saccharomyces cerevisiae Depends on the Direction of Replication and the RAD50 and RAD52 Genes

Abstract: Small direct repeats, which are frequent in all genomes, are a potential source of genome instability. To study the occurrence and genetic control of repeat-associated deletions, we developed a system in the yeast Saccharomyces cerevisiae that was based on small direct repeats separated by either random sequences or inverted repeats. Deletions were examined in the LYS2 gene, using a set of 31- to 156-bp inserts that included inserts with no apparent potential for secondary structure as well as two quasipalindr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
119
2
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(136 citation statements)
references
References 53 publications
14
119
2
1
Order By: Relevance
“…This result is consistent with other recent reports showing genetic instability in cells with mutations in DNA polymerases or replication-associated proteins (51)(52)(53)). An increased frequency of direct repeat-associated deletions was also reported with a temperature-sensitive pol ␣ allele in Schizosaccharomyces pombe (52).…”
Section: E Coli and Yeast Complementationsupporting
confidence: 83%
“…This result is consistent with other recent reports showing genetic instability in cells with mutations in DNA polymerases or replication-associated proteins (51)(52)(53)). An increased frequency of direct repeat-associated deletions was also reported with a temperature-sensitive pol ␣ allele in Schizosaccharomyces pombe (52).…”
Section: E Coli and Yeast Complementationsupporting
confidence: 83%
“…However, studies of DNA replication and double-strand break formation during meiosis reveal a significant temporal overlap between these reactions (Padmore et al 1991) suggesting that a mechanism exists to ensure that cleavage occurs after replication. Whether DNA secondary structure plays any part in the generation of double-strand breaks in yeast is unknown but rad50 mutants reverse the instability of inverted repeats observed in a pol3 mutant (Gordenin et al 1992;Tran et al 1995). These results also suggest a role for RAD50 in DNA replication (Tran et al 1995).…”
Section: Genetic Recombinationmentioning
confidence: 78%
“…Pol32 is a subunit of DNA Polδ and the deletion of the POL32 gene results in reduced Polδ processivity and a compromised DNA damage response [39]. Similarly, in a strain with mutation in the major catalytic subunit of the Polδ (pol3-t mutant), a large orientationindependent increase in the deletion frequency of sequences flanked by 6-7 bp direct repeats has been reported [40]. It has been suggested that large dels reflect the inherent single-stranded character of the lagging-strand template, which would be expected to be further enhanced if polymerization is compromised, allowing the formation of misaligned slippage intermediates between nontandem direct repeats [41].…”
Section: Discussionmentioning
confidence: 98%